Comparative study of IoT- and AI-based computing disease detection approaches - Wasiur Rhmann; Jalaluddin Khan; Ghufran Ahmad Khan; Zubair Ashraf; Babita Pandey; Mohammad Ahmar Khan; Ashraf Ali; Amaan Ishrat; Abdulrahman Abdullah Alghamdi; Bilal Ahamad; Mohammad Khaja Shaik (Data Science and Management)
The emergence of different computing methods such as cloud-, fog-, and edge-based Internet of Things (IoT) systems has provided the opportunity to develop intelligent systems for disease detection. Compared to other machine learning models, deep learning models have gained more attention from the research community, as they have shown better results with a large volume of data compared to shallow learning. However, no comprehensive survey has been conducted on integrated IoT- and computing-based systems that deploy deep learning for disease detection. This study evaluated different machine learning and deep learning algorithms and their hybrid and optimized algorithms for IoT-based disease detection, using the most recent papers on IoT-based disease detection systems that include computing approaches, such as cloud, edge, and fog. Their analysis focused on an IoT deep learning architecture suitable for disease detection. It also recognizes the different factors that require the attention of researchers to develop better IoT disease detection systems. This study can be helpful to researchers interested in developing better IoT-based disease detection and prediction systems based on deep learning using hybrid algorithms.